PENGEMBANGAN STRATEGI INVESTIGASI KRITIS UNTUK PEMBELAJARAN MENULIS TEKS EKSPOSISI - Draditaswari, Silka Yuanti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research and development aims to produce the strategy of critical investigation on writing teaching expository text in the eight grade of junior high school with valid criterion in theory, coherent, practical, and effective in terms of application. To develop the strategy on teaching writing, use the method of development and research of adapted Borg and Gall with the method of developing a Kemp learning strategy. Based on the result of feasibility test and effectiveness test, it is obtained that the product is feasible to be used with valid percentage 95%, 86% coat, and practical 81%. The product is also effectively used with a significance value of 0.000. Thus the product has a significant influence on the learning result of expository text writing.